2017
DOI: 10.1136/bmjspcare-2016-001125
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the effectiveness, barriers and facilitators to general practitioner engagement with specialist secondary services in integrated palliative care

Abstract: This is an emerging field and further research is required assessing the effectiveness of different models of integrated palliative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 23 publications
2
64
0
Order By: Relevance
“…9 Exploring GPs' views on best practice palliative care can inform healthcare delivery Several studies have sought GPs' perceptions of barriers and enablers to the delivery of best practice palliative care. [10][11][12][13][14] There have also been a number of policy papers highlighting the important features of delivering best practice palliative care. 5,15 However, most GPs are still self-defining their role in palliative care delivery.…”
Section: Introductionmentioning
confidence: 99%
“…9 Exploring GPs' views on best practice palliative care can inform healthcare delivery Several studies have sought GPs' perceptions of barriers and enablers to the delivery of best practice palliative care. [10][11][12][13][14] There have also been a number of policy papers highlighting the important features of delivering best practice palliative care. 5,15 However, most GPs are still self-defining their role in palliative care delivery.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic literature review 2 showed that in countries such as Australia, New Zealand, Canada and countries of Europe, where medical records of patients are shared by the health systems, the choice of actions and care measures in during emergency calls are facilitated. The study also emphasized that when the information is integrated between primary care and specialized PC services, positive factors are observed in terms of less repeated admissions and shortest hospital stay, besides relevant improvements in pain control and other symptoms and, consequently, improved QOL for patients.…”
Section: Discussionmentioning
confidence: 99%
“…What are the limitations and possibilities that you nd when providing this type of assistance in the emergency service? (2) In emergency services, professionals seek to save lives. Do you think you are prepared to 'deal' with the death of a terminally ill patient during a call in which the SAMU is requested to promote comfort and/or pain relief at that moment?…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations